'Where Cassius Clay Ends, Muhammad Ali Begins': Sportspeople, Political Activism, and Methodology. Issue 11 (24th July 2018) - Townsend, Stephen; Osmond, Gary; Phillips, Murray G.
Abstract: Muhammad Ali's refusal to be drafted into the United States Army in June 1967 led to a conviction for draft evasion, exile from boxing, and a complex response from the newspaper press. Although press reactions to Ali's draft resistance were overwhelmingly negative, his refusal to fight in Vietnam sowed the seeds for journalists to celebrate him as a hero upon his return to the ring four years later. Press reactions to Ali's two names (Cassius Clay and Muhammad Ali) act as a lens for scrutinizing this attitudinal shift. This investigation involved macro and micro analyses of 12 United States newspapers. First, distant reading techniques were used to reveal distinct temporal patterns in the usage of both names. In September 1967, journalists from these publications began to use Ali's two names far more interchangeably than they previously had. By March 1971, they had fully embraced Ali's Muslim name over his birth name. Close reading then revealed how and why these patterns developed: changes to Ali's persona, as well as broader cultural and political forces, prompted newspaper journalists to accept his chosen name and identity in early 1971.